SLOW RELEASE FERTILIZER ON THE GROWTH OF SEEDLINGS Anadenanthera peregrina (L.) Speg. AND Schinus terebinthifolius Raddi - Rossa, Überson Boaretto (2015)
http://dx.doi.org/10.5902/1980509820582In order to assess the development of two native species, Anadenanthera peregrina and Schinus terebinthifolius, submitted to doses of slow-release fertilizer formulation 13-06-16, an experiment was conducted in greenhouse using a mixture of raw materials with organic compost, vermiculite and plantmax to compose base substrate. The experiment was conducted in a completely randomized design with six treatments and four replications. The treatments were : T1-0 kg (control), T2-2 kg, 4 kg-T3 , T4-6 kg,  T5-8 kg and T6 – 10 kg slow release fertilizer per cubic meter of base substrate . Was evaluated at 189 days after sowing the total height, stem diameter, fresh weight of shoot, dry shoot biomass, root dry biomass, total biomass, the relationship between height and stem diameter and quality index Dickson. The results suggest that application of slow release fertilizer leads to significant gains in growth in both species, with the best doses from 6.68 to 5.54 kg m-3 for Anadenanthera peregrina species, and from 8.38 to 14,42 kg m-3 for Schinus terebinthifolius.